2005
DOI: 10.1196/annals.1345.062
|View full text |Cite
|
Sign up to set email alerts
|

Fertility and Pregnancy in Thalassemia Major

Abstract: Over the last 15 years, 22 women with thalassemia major have completed 29 pregnancies at the Royal Hospital in London. The major pre-pregnancy issues, medications, and pregnancy care are reviewed. Experience suggests that, with proper care and guidance, pregnancies among women with thalassemia major are practical and can have successful outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 2 publications
0
37
0
3
Order By: Relevance
“…[8][9][10][11] Apart from the report by Skordis et al, who described the pregnancies of 86 women with thalassemia major and 12 women with thalassemia intermedia from Greece, only a small number of studies have focused on pregnancy in well-transfused and well-chelated women with thalassemia major. [12][13][14][15] Moreover, only a few studies have been published describing pregnancy in women with thalassemia intermedia. 16 There are reports of increased risk of abortion, pre-term delivery, intrauterine growth restriction and thromboembolism in pregnant women with thalassemia intermedia.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] Apart from the report by Skordis et al, who described the pregnancies of 86 women with thalassemia major and 12 women with thalassemia intermedia from Greece, only a small number of studies have focused on pregnancy in well-transfused and well-chelated women with thalassemia major. [12][13][14][15] Moreover, only a few studies have been published describing pregnancy in women with thalassemia intermedia. 16 There are reports of increased risk of abortion, pre-term delivery, intrauterine growth restriction and thromboembolism in pregnant women with thalassemia intermedia.…”
Section: Introductionmentioning
confidence: 99%
“…More and more adult thalassemic patients in their second and third decades of life with the prospect of marriage wish to know their ability to father a child (3,4,14,(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Conventional semen analysis was carried out using manual procedures and light microscopy in the central hospital laboratory according to the last World Health Organization guidelines (20). The semen analyzer was blinded to patients' names and diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…Two recent prospective large-scale studies confirmed the efficacy of DFX in reducing serum ferritin levels and total body iron stores in patients with thalassemia [1,2], and therefore the use of DFX is quite common among thalassemic patients. In addition, there is growing evidence from specialist centers that the number of women affected by thalassemia major with spontaneous ovulation and unplanned pregnancies is increasing [3,4,5,6,7]. Thus, it is not surprising that spontaneous pregnancy can occur in well-chelated and transfused thalassemic patients, but the interesting features of this case, which have never been reported previously, are both the advanced maternal age and the concomitant and well-tolerated administration of DFX chelation therapy.…”
Section: Discussionmentioning
confidence: 99%